BORROWING COMPLEX WORDS IN ENGLISH AND UZBEK LANGUAGES (BASED ON MEDICAL SCIENCES): SEMANTIC ASPECT. (Journal of Universal Science Research, 2024)
This article examines how complex medical terms are borrowed into English and Uzbek, focusing on their meanings. Medical terms, often from Latin and Greek, can be difficult to integrate into new languages. By looking at specific examples, the research shows how these terms are changed to fit the sounds and meanings of English and Uzbek. The study finds patterns in how medical vocabulary is adopted and adapted, helping us understand how languages evolve with new scientific words. This research sheds light on the interaction between global medical terminology and local languages.